Public-Private Partnership for Skill Acquisition and Vocational Technical Education Development in Nigeria - Okpor, Ikechukwu; Najimu, Hassan (Richtmann Publishing, 2012)
This paper discusses the Private Sector Partnership with Education for Skill Acquisition and Vocational TechnicalEducation Development. The relevance of the partnership on bringing skilled and trained manpower in their area ofspecialization is for the purpose of national development and self actualization. Strategies were identified for the effectiveness ofthe programme.